Defining clinico-neuropathological subtypes of mesial temporal lobe epilepsy with hippocampal sclerosis - Blümcke, Ingmar; Coras, Roland; Miyata, Hajime; Özkara, Cigdem (Brain Pathology, 2012)
Hippocampal sclerosis (HS) is the most frequent cause of drug-resistant focal epilepsies (ie, mesial temporal lobe epilepsy with hippocampal sclerosis; mTLE-HS), and presents a broad spectrum of electroclinical, structural and molecular pathology patterns. Many patients become drug resistant during the course of the disease, and surgical treatment was proven helpful to achieve seizure control. Hence, up to 40% of patients suffer from early or late surgical failures. Different patterns of hippocampal cell loss, involvement of other mesial temporal structures, as well as temporal neocortex including focal cortical dysplasia, may contribute to the extent of the epileptogenic network and will be discussed. An international consensus is mandatory to clarify terminology use and to reliably distinguish mTLE-HS subtypes. High-resolution imaging with confirmed histopathologic diagnosis, as well as advanced neurophysiologic and molecular genetic measures, will be a powerful tool in the future to address these issues and help to predict each patient's probability to control their epilepsy in mTLE-HS conditions. © 2012 The Authors; © 2012 International Society of Neuropathology.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Development; Hippocampus; Mesial temporal sclerosis; Neuropathology; Seizure